Ludic Function of Precedent-Related Phenomena in Media Discourse - Velykoroda, Yu. (Journal of Vasyl Stefanyk Precarpathian National University, 2016)
The aim of this paper is to determine the ludic function of precedent-related phenomena as a type of intertextuality. The analysis is done on the basis of relevance theoretic approach, through which we aim to show the additional cognitive effect which is created by precedent-related phenomena in media discourse, and this comic effect serves as a foundation for the ludic function of these units